Pengaturan dan Tanggung Jawab Penyedia Jasa Layanan Komputasi Awan (Cloud Computing) atas Penyimpanan Data Pribadi Pengguna dari Kebocoran Data Elektronik - Jesline Arsjad; Sinta Dewi Rosadi; Rika Ratna Permata (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
The rapid development of information technology that provides benefits turns out to have a negative impact on users, the possibility of personal data leakage. Cloud Computing is one example of the development of information technology (IT) that offers real convenience in storing, uploading, and downloading data. However, a few phenomenon involves the platform in the case of data leaks. The purpose of this research is to identify the arrangements and the responsibility of cloud computing service providers. Cloud computing is implicitly regulated in the Constitution of electronic information and transaction (UU ITE) and 2019 Government regulations on the Operation of Electronic Systems and Transactions (PP PSTE 2019), the registration of a reliability certificate to ensure its security. PP PSTE 2019 allows Electronic System Operator (PSE) to do storage both inside and outside Indonesia but is under the supervision of the ministry so it is understandable that cloud computing is regulated in Indonesia in the sense of storage. The law is progressive and does not comply with cloud computing regulations that have not been specifically regulated.